Pengaruh variasi besar lubang dan tebal plat terhadap boiling time, lama nyala dan laju pembakaran pada desain kompor biomassa tongkol jagung - Joniarta, I.W.; Wijana, M. (Dinamika Teknik Mesin: Jurnal Keilmuan dan Terapan Teknik Mesin, 2018)
The biomass stove is designed to utilize fuel chunks.  The main principle of the stove design is to utilize the outside air coming into the stove through the hole on the underside. The air coming into the stove is divided becoming primary air and secondary air. The primary air enters from under the burning sleeve to the fuel, while the secondary air enters from the top hole of the burning sleeve and burns the combustion gas containing fuel-burning substances. In this study, the fuel used was corncob with a diameter of 3-4 cm, a length of 6-7 cm, and moisture contents ranging from 14%-16%. The stove used consists of 8 variations of the design model. Independent variables in this study were plate thickness, outer air hole diameter, secondary air hole diameter, and primary air hole diameter. While the dependent variables investigated were boiling time and flaming duration. The fastest boiling time was 2.07 minutes achieved from the stove designed no 3. Meanwhile, The longest flaming duration was 13.24 minutes shown by the stove no 6. There for the fastest burning rate was 0,00708 kg/s was sown  stove designed no 6, and the latest burning rate  was 0,00474 kg/s  achieved from the stove no 6. This different result is influenced by the density of the corncobe, the density of the biomass fuel  will be quikly burned and very fast oxidation.